﻿Myrtus communis in Europe threatened by the pandemic and South African strains of the myrtle rust pathogen Austropuccinia psidii (Sphaerophragmiaceae, Pucciniales) - Trudy Paap; Alberto Santini; Carlos A. Rodas; Ginna M. Granados; Francesco Pecori; Michael J. Wingfield (NeoBiota, 2023)
Austropuccinia psidii, the causal agent of myrtle rust, has emerged as a significant threat to Myrtaceae in planted and natural woody ecosystems. The first detection of A. puccinia in South Africa was from severely infected ornamental Myrtus communis. This raised concern that M. communis, the sole Myrtaceae species native to Europe and an important component of vegetation in Mediterranean regions, could be threatened by the rust. In light of the potential threat to this unique species, seed was collected from 12 Italian provenances of M. communis, including mainland and island (Sardinia and Sicily) populations. We assessed the susceptibility of these provenances to both the pandemic and South African strains of A. psidii. In Colombia, where the pandemic strain of A. psidii is native, seedlings rapidly became infected by natural inoculum. In South Africa, a preliminary screening of seedlings by artificial inoculation with a single-uredinium isolate produced high levels of disease. Finally, plants of each of the 12 provenances were planted and monitored in Florence, Italy. To date, these showed no signs of disease, but will continue to be monitored. This study highlights the significant threat that both the pandemic and South African strains of A. puccinia pose to M. communis in Europe.